More than stigma: Interrogating counter narratives of abortion. (October 2019) - Baird, Barbara; Millar, Erica
A large body of feminist scholarship identifies and examines modes of representing abortion, focusing on themes such as stigma and the production of an autonomous foetal subject. In recent years, there has been a proliferation of cultural representations of abortion that do not conform with, and even explicitly reference and rebuke, stigmatising and foetocentric depictions of abortion. Focusing on the Australian context and two sets of online sites—the websites of Australian abortion clinics and widely circulated pro-choice, feminist commentary on abortion—this article provides a critical reading of new, 'unapologetic' modes of representing abortion. We argue that they increase the cultural legitimacy of abortion and are therefore incredibly important, but have limitations because of their reification of the neoliberal autonomous subject. Nevertheless, we urge feminist scholars to pay more attention to discourses that presume abortion is unproblematic and beneficial to women. Scholarship on abortion has performative effects, and we hope that identifying and nurturing counter narratives of abortion is one means by which abortion can be normalised.